2014
DOI: 10.1080/10463283.2014.982948
|View full text |Cite
|
Sign up to set email alerts
|

Improving intergroup relations with extended and vicarious forms of indirect contact

Abstract: Research in social psychology has provided impressive evidence that intergroup contact reduces prejudice. However, to the extent that strategies based on direct contact are sometimes difficult to implement, scholars have more recently focused on indirect contact. An effective form of indirect contact is extended contact. According to the extended contact hypothesis, simply knowing that ingroup members have outgroup friends (extended contact), or observing these friendships vicariously (vicarious contact), can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
320
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(351 citation statements)
references
References 133 publications
12
320
0
5
Order By: Relevance
“…Indeed, the mere knowledge that an ingroup member has a close relationship with an outgroup member can reduce prejudice (i.e., extended contact; Wright, Aron, Mclaughlin-Volpe, & Ropp, 1997; see also Dovidio, Eller, & Hewstone, 2011). A recent review uncovering more than 90 studies revealed that extended contact has widespread effects spanning across several outcome variables, target-groups, contexts and age-groups, thus supporting its role as an effective strategy to reduce prejudice (Vezzali, Hewstone, Capozza, Giovannini, & Wölfer, 2014). Notably, both direct (Fingerhut, 2012;Heinze & Horn, 2009;Lemm, 2006;West & Hewstone, 2012) and extended (Capozza, Falvo, Trifiletti, & Pagani, 2014;Hodson, Harry, & Mitchell, 2009;Mereish & Poteat, in press;Sharp, Voci, & Hewstone, 2011) contact have been shown to be effective means to improve attitudes towards homosexuals.…”
Section: Direct and Extended Intergroup Contactmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the mere knowledge that an ingroup member has a close relationship with an outgroup member can reduce prejudice (i.e., extended contact; Wright, Aron, Mclaughlin-Volpe, & Ropp, 1997; see also Dovidio, Eller, & Hewstone, 2011). A recent review uncovering more than 90 studies revealed that extended contact has widespread effects spanning across several outcome variables, target-groups, contexts and age-groups, thus supporting its role as an effective strategy to reduce prejudice (Vezzali, Hewstone, Capozza, Giovannini, & Wölfer, 2014). Notably, both direct (Fingerhut, 2012;Heinze & Horn, 2009;Lemm, 2006;West & Hewstone, 2012) and extended (Capozza, Falvo, Trifiletti, & Pagani, 2014;Hodson, Harry, & Mitchell, 2009;Mereish & Poteat, in press;Sharp, Voci, & Hewstone, 2011) contact have been shown to be effective means to improve attitudes towards homosexuals.…”
Section: Direct and Extended Intergroup Contactmentioning
confidence: 94%
“…In particular, research on direct contact has mostly focused on affective mediators such intergroup anxiety (see Brown & Hewstone, 2005;Pettigrew & Tropp, 2008), whereas research on extended contact has mainly considered cognitive mediators such as ingroup and outgroup norms (see Vezzali et al, 2014). A c c e p t e d M a n u s c r i p t 5 More recently, it has been shown that morality has a leading role in shaping outgroup impressions (for a review, see Brambilla & Leach, 2014).…”
Section: Moral Purity As a Mediator Of Contact Effectsmentioning
confidence: 99%
“…This study is also among the first (see Vezzali et al, 2014) The two immigrant groups differ in social status in Finnish society and these differences are reflected mostly in their position in the labour market and attitudes towards these groups among majority Finns. In 2013, the unemployment rate among Russian immigrants (15 %) was twice as high as among Estonian immigrants (8 %) and three times higher than among majority Finns (5 %) (Statistics Finland, 2014).…”
Section: Overview Of the Present Studiesmentioning
confidence: 89%
“…To the best of our knowledge, our studies are the first to test whether interminority extended contact is associated with more positive attitudes towards other minority groups. Moreover, we aimed at detecting whether the aforementioned relationship is mediated by affective (outgroup empathy; Study 1, and outgroup trust; Study 2) and cognitive (ingroup norm; Study 2) processes, as suggested by previous INTERMINORITY EXTENDED CONTACT 4 research among majorities and minorities (for a review, see Vezzali, Hewstone, Capozza, Giovannini, & Wölfer, 2014).…”
Section: Interminority Extended Contactmentioning
confidence: 99%
“…These efforts can be seen as ways to make the unfamiliar familiar and line up with the intergroup contact hypothesis[9]. Deliberate interpersonal contact has long been one of the most influential strategies for improving relations between groups that are unfamiliar with each other[10] and an effective way to reduce prejudice between majority and minority group members[11]. Scholars have proposed that such a positive effect may only be expected under appropriate conditions[12,13] including sufficient knowledge, equal status between groups, interdependent goals, intergroup cooperation, personal and positive contact, an instilment of the positive experience in attitudes towards the other group, and the support of the involved institutions and authorities [9,14].…”
Section: Introductionmentioning
confidence: 99%